Nuevo registro de vertebrados para la Formación Aconquija, provincia de Catamarca, Noroeste de Argentina. Implicancias cronoestratigráficas y consideraciones paleoambientales - Nasif, Norma L.; Esteban, Graciela; Georgieff, Sergio M. (Acta Geológica Lilloana, 2008)
“New record of vertebrates from the Aconquija Formation, Catamarca province, Northwest of Argentina. Chronostratigraphic implications and palaeoenvironmental approachs”. A new vertebrate’s record for Neogene of Catamarca Province, Northwest of Argentina is registered. The fossils are a small rodent and a big ground sloth coming from the lower section of Aconquija Formation, which crops out along the El Durazno Creek at Las Estancias Valley (27º26’S – 66º00’W y 27º40’S – 66º00’W). The fossils are assigned to Microcavia sp. (Hystricognathi, Caviidae, Caviinae) and Mylodontinae indet. (Xenarthra). Aconquija Formation is correlated with the Santa María Group in the homonymous valley (further to northwest of the study area), then the age corresponds to Middle Miocene to Pliocene. Microcavia sp. is the first fossil record of this genus for the Northwest of Argentina and allows to extend its biochron to Upper Early Miocene, this is the more antique of Microcavia . A new species of Microcavia , for this period of the Northwest of Argentina, is inferred since that the new specimen presents different features than the rest of the species known.